2017
DOI: 10.1002/elan.201700525
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Active Pd‐In/three‐dimensional Graphene with Special Structure for Electroreduction CO2 to Formate

Abstract: Electrocatalytic reduction of CO 2 to formate on carbon based electrodes is known to suffer from low electrochemical reaction activity and product selectivity. Pd/three-dimensional graphene (Pd/3D-RGO), In/3D-RGO and Pd-In/3D-RGO for the electrochemical reduction of CO 2 were prepared by a mild method that combines chemical and hydrothermal. The metal/3D-graphenes (metal/3D-RGO) were characterized by scanning electron microscopy, X-ray diffraction, transmission electron microscopy and X-ray photoelectron spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…As compared to Pd/3D-RGO or In/3D-RGO, the Pd 0.5 -In 0.5 /3D-RGO catalyst showed the highest Faradaic efficiency for formate (85.3 %) and was stable for 24 h at À 1.6 V vs. Ag/AgCl in 0.5 M KHCO 3 electrolyte. [113] The improved catalytic performance was considered to be related to the small particle size (12.80 � 0.05 nm) and high particle dispersion.…”
Section: Pd-inmentioning
confidence: 99%
“…As compared to Pd/3D-RGO or In/3D-RGO, the Pd 0.5 -In 0.5 /3D-RGO catalyst showed the highest Faradaic efficiency for formate (85.3 %) and was stable for 24 h at À 1.6 V vs. Ag/AgCl in 0.5 M KHCO 3 electrolyte. [113] The improved catalytic performance was considered to be related to the small particle size (12.80 � 0.05 nm) and high particle dispersion.…”
Section: Pd-inmentioning
confidence: 99%
“…For instance, an electrically conductive and porous 3D graphene network has been prepared via mild chemical reduction of GO by sodium bisulfide at 95°C under atmospheric pressure and in the presence of iron oxide nanoparticles [43]. He et al [44] reported the facile fabrication of 3D graphene sponges containing palladium and indium by combination of the hydrothermal and chemical reduction techniques. In this study, GO aqueous solution containing palladium and indium salts and vitamin C as reducing agent were treated hydrothermally at 110°C for 6 h.…”
Section: Self-assembly Methodsmentioning
confidence: 99%
“…The Pd/three-dimensional graphene-based catalyst (Pd/3D-rGO), In/3D-rGO and Pd-In/3D-rGO) for CO 2 RR to formate were prepared by chemical and hydrothermal methods. The most optimal nanocatalyst, Pd 0.5 -In 0.5 /3D-rGO, with a particle size of 12.8 nm, demonstrates a high Faradaic efficiency of 85.3% at 1.6 V (Ag/AgCl) and a peak potential of 0.70 V (Ag/AgCl), which is more positive than In1.0/3D-RGO (−0.73 V) and Pd1.0/3D-RGO (−1.2 V) [106].…”
Section: Noble Metal 3d Graphene-based Nanocomposite (Nnm3dgc)mentioning
confidence: 96%
“…This work reviewed recent progress in three-dimensional (3D) cathodes for CO 2 reduction. In the literature, these cathodes have been either purposely constructed to be three-dimensional, or have had the potential to serve as three-dimensional [104][105][106][107][108]. 3D cathodes with hierarchically porous nanostructures offer many benefits, and are one of the most effective strategies to resolve the abovementioned challenges [109][110][111][112][113][114][115][116].…”
Section: Introductionmentioning
confidence: 99%